Interprofessional Education: A Basic Need of Healthcare Department in Pakistan - Rehman, Saif Ur; Ali, Fahad; Usman Ahmad, Muhammad (International Journal of Biotechnology for Wellness Industries, 2017)
Inter professional education (IPE) is the core concept of healthcare department in most of the developed countries on both student and professional level. There is no objection on its necessity. Top ranking universities of the world, especially of developed countries are working on IPE. But some of developing countries like Pakistan are almost unaware of this concept. No one is having the basic concept of IPE, except few, and they are not practicing in IPE so far. Talking about Punjab, there is no awareness for the concept of IPE. It is the need of our healthcare department that we must introduce IPE to improve healthcare quality. This survey was conducted to check the readiness for IPE among pharm D and MBBS students in different institutes of medicine and pharmacy of Lahore. Team went to different pharmacy and medical colleges and asked the students to fill in a questionnaire having 19 items, which was rated by the students on Likert scale. The result shows a conflict in the opinion of pharmacy and medical students. Team also interviewed the respondents shortly. This interview showed many reasons explained by medical students for their response but the most prominent one was the superiority complex. The need of the hour is to introduce IPE in universities for changing the attitude of medical students towards IPE.